Mycotoxilogical monitoring. Part 2. Wheat, barley, oat and maize grain - G. P. Kononenko; A. A. Burkin; Ye. V. Zotova (Ветеринария сегодня)
Results of mycotoxicological survey of representative samples of feed and procured wheat, barley, oat and maize grain batches are demonstrated. The samples were submitted by the Veterinary Service officials, livestock farmers and feed mill operators, agricultural producers, specialized commercial business operators and farm owners in seven Federal Districts of the Russian Federation in 2009-2019. Similar amounts of wheat and barley grain samples were received from the Central, Volga, Ural and Siberian Federal Districts. The amount of wheat samples delivered from the Southern Federal District prevailed over the number of barley samples, and the maize samples were mostly delivered from the regions of the Central Federal District. Fusarium toxins including T-2 toxin, diacetoxyscirpenol, deoxynivalenol, zearalenone and fumonisins of group B as well as alternariol, ochratoxin A, citrinin, aflatoxin В1, sterigmatocystin, cyclopiazonic acid, mycophenolic acid, ergot alkaloids and emodin were detected and measured according to the validated competitive ELISA procedure. Generalization of the results demonstrated domination of fusarium toxins and active involvement of alternariol in the contamination of all types of feed grains as well as high occurrence of emodin in ear cereals and increased occurrence of T-2 toxin and ochratoxin A in barley. Shift of medians and 90%-percentile of the basic contaminants to lower values as compared to mean and maximal ones was reported thus being indicative of their possible accumulation at the levels outside the typical range. The highest levels of T-2 toxin, deoxynivalenol and ochratoxin A as well as 90%-percentile values exceeded the acceptable levels. The maize grains demonstrated the whole complex of the tested fusarium toxins with the prevalence of T-2 toxin, deoxynivalenol, zearalenone and fumonisins; and the maximal amounts of these mycotoxins by several times exceeded the accepted regulatory levels. Diacetoxyscirpenol, aflatoxin В1, sterigmatocystin, cyclopiazonic acid and ergot alkaloids are classified as rare feed grain contaminants. High prevalence of alternariol and emodin known as “diarrhea factor” as well as maize grain contamination with mycophenolic acid (mycotoxin having an immunosuppressive effect) are for the first time reported in this paper. These data support the need of their introduction in the group of regulated substances significant for public health. Original monitoring data systematized and summarized in the paper are given in electronic format in section Additional materials.Part 1: Veterinary Science Today. 2020; 1 (32): 60–65. DOI: 10.29326/2304-196X-2020-1-32-60-65.